2012
DOI: 10.2147/ceg.s30281
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 immunoreactivity in colorectal neoplasia

Abstract: IntroductionMicrotubule-associated doublecortin and CaM kinase-like-1 (DCLK1) is a novel candidate marker for intestinal stem cells. The aim of our study was to assess DCLK1 immunoreactivity in colorectal carcinogenesis and its correlation with prognosis.MethodsDCLK1 immunostaining was performed in colorectal tissue from 71 patients, including 18 adenomatous polyps, 40 primary adenocarcinomas, and 14 metastatic lesions. Each case was evaluated by a combined scoring method based on the intensity of staining (sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 23 publications
3
58
2
Order By: Relevance
“…In a subset of human colorectal cancers and high-grade adenomas strong Dclk1 protein expression is associated with disease recurrence but not with disease stage, suggesting that Dclk1 expression was an independent prognostic factor. 38,39 However, Dclk1 gene expression was significantly downregulated in a large number of colorectal cancer samples and cell lines, most likely through hypermethylation of the Dclk1 promoter. 40 Recently, Singh and colleagues were able to shed light on the complex epigenetic regulation of different Dclk1 transcripts in colorectal cancer, and showed that expression of a long Dclk1 isoform, transcribed from the 5' promoter, is silenced in colorectal cancer due to hypermethylation at this site.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 99%
“…In a subset of human colorectal cancers and high-grade adenomas strong Dclk1 protein expression is associated with disease recurrence but not with disease stage, suggesting that Dclk1 expression was an independent prognostic factor. 38,39 However, Dclk1 gene expression was significantly downregulated in a large number of colorectal cancer samples and cell lines, most likely through hypermethylation of the Dclk1 promoter. 40 Recently, Singh and colleagues were able to shed light on the complex epigenetic regulation of different Dclk1 transcripts in colorectal cancer, and showed that expression of a long Dclk1 isoform, transcribed from the 5' promoter, is silenced in colorectal cancer due to hypermethylation at this site.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 99%
“…As a negative control, the primary antibody was replaced with serum immunoglobulin G (GTX35035; GeneTex, Inc., Irvine, CA, USA) at the same dilution. A CIA sample from the total cohort exhibiting strong intensity immunostaining for DCLK1, defined by the staining evaluation method of a previous study (13), was used as a positive control. For each specimen, at least five fields were viewed under a light microscope (magnification, x100; Olympus Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The extent (or proportion) of DCLK1 staining was scored as: 0 (<5% positive cells), 1 (5-30% positive cells), 2 (31-60% positive cells) or 3 (61-100% positive cells); the staining intensity was scored as: 0 (negative), 1 (mild), 2 (moderate) or 3 (strong), as previously described (13). The final score was determined from the combination of the staining intensity and proportion scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have demonstrated DCLK1 expression in multiple types of solid tumor, including colon, intestinal and pancreatic cancer, and HCC (20,(25)(26)(27). In addition, it has been revealed that patients with a high (>4) DCLK1 staining score are associated with increased cancer-specific mortality rates compared with those with a low (0-4) DCLK1 staining score in colorectal neoplasia (27). To the best of our knowledge, no study has been performed to assess the association between DCLK1 expression and survival outcome in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%